Study on downtime calculation considering a series of seismic sequences in resilience performance assessment of RC buildings - Motobe, Taiyo; Takahashi, Noriyuki (Frontiers in Built Environment, 2026)
Current seismic design primarily targets life safety under rare major earthquakes, while recent societal demands emphasize seismic resilience, particularly timely functional recovery and reduction of downtime. However, most existing downtime assessment frameworks implicitly assume that damage is governed by a single mainshock and do not explicitly track cumulative deterioration caused by repeated moderate earthquakes over the building’s service life. This omission can underestimate the downtime associated with the life-cycle maximum event. This study proposes a downtime evaluation method for RC office buildings that explicitly incorporates (1) delay times due to impeding factors, (2) repair times of structural components, (3) repair times of nonstructural components, and, as a distinctive feature, (4) cumulative deterioration induced by annual moderate earthquakes within a life-cycle seismic hazard framework. Five-, seven-, and ten-story shear-spring models with three ultimate ductility levels (strength-type, standard-type, and ductile-type) are analyzed under annual ground motion sequences consistent with the seismic hazard at Aobayama, Sendai, including both a single strong-motion record and a combined strong-motion sequence from the 2016 Kumamoto Earthquake. Structural damage is quantified using the Park and Ang damage index, nonstructural damage is evaluated via fragility curves, delay times are modeled with lognormal distributions for each impeding factor, and downtime is obtained from repair sequencing along multiple repair paths using Monte Carlo simulations. Results show that cumulative deterioration from moderate earthquakes, when propagated to the time of the life-cycle maximum event, systematically increases both damage indices and downtime compared with conventional mainshock-only assessments. Ductile-type models effectively limit this downtime growth in low-to mid-rise buildings. In particular, for the seven-story building subjected to the combined strong-motion sequence, converting the frame from the strength-type to the ductile-type reduces the estimated downtime by 17.3%. Although the average downtime is similar among the three building heights, the story-wise concentration of damage and the configuration of repair phases differ, indicating that explicitly modeling cumulative deterioration, together with optimized repair phasing and ductile design, is essential for reliably assessing and reducing downtime in resilience-oriented design of RC buildings.